2019
DOI: 10.1021/acs.jmedchem.8b01987
|View full text |Cite
|
Sign up to set email alerts
|

New Quinolylnitrones for Stroke Therapy: Antioxidant and Neuroprotective (Z)-N-tert-Butyl-1-(2-chloro-6-methoxyquinolin-3-yl)methanimine Oxide as a New Lead-Compound for Ischemic Stroke Treatment

Abstract: We describe herein the synthesis and neuroprotective capacity of an array of 31 compounds comprising quinolyloximes, quinolylhydrazones, quinolylimines, QNs, and related heterocyclic azolylnitrones. Neuronal cultures subjected to oxygen−glucose deprivation (OGD), as experimental model for ischemic conditions, were treated with our molecules at the onset of recovery period after OGD and showed that most of these QNs, but not the azo molecules, improved neuronal viability 24 h after recovery. Especially, QN (Z)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(86 citation statements)
references
References 60 publications
6
80
0
Order By: Relevance
“…Taking into account the properties of the various fluorophores, the quinoline skeleton has attracted our great interest because of its drug-like physicochemical and photophysical properties. Previously, the quinoline derivatives have shown that the desired BBB penetrability can be applied for the development of brain imaging or neuroprotective agents (41)(42)(43)(44)(45). For example, a quinolone-based Schiff base can serve as a staining reagent for imaging metal ions (Cu 2+ and Zn 2+ ) in Aβ plaques; quinolylnitrones can be used as the potential neuroprotective agents (SI Appendix, Scheme S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the properties of the various fluorophores, the quinoline skeleton has attracted our great interest because of its drug-like physicochemical and photophysical properties. Previously, the quinoline derivatives have shown that the desired BBB penetrability can be applied for the development of brain imaging or neuroprotective agents (41)(42)(43)(44)(45). For example, a quinolone-based Schiff base can serve as a staining reagent for imaging metal ions (Cu 2+ and Zn 2+ ) in Aβ plaques; quinolylnitrones can be used as the potential neuroprotective agents (SI Appendix, Scheme S1).…”
Section: Resultsmentioning
confidence: 99%
“…After i.v. injection of HCP (0.5 mg/kg), in vivo imaging showed that the fluorescence intensity of the epilepsy group in the brain regions was significantly higher than that in WT healthy mice at different times (5,15,30,45, and 60 min), clearly demonstrating HCP can effectively cross the BBB and track the up-regulation of HClO in the brain. Particularly, pre/posttreatment with apigenin, the mouse brains showed reduced fluorescence signals compared to those treated with KA alone (Fig.…”
Section: Imaging In Live Cells With Hcp Under Glutamate\kainic Acid-imentioning
confidence: 96%
“…The grip strength test is designed to assess the maximum force in the mouse’s forelimbs using a metal grid connected to a force sensor (Bioseb, Vitrolles, France). The test was performed as described previously [26,33,34] and a total of 6 trials were carried out in each test session, calculating the strength (in grams) as the mean of these trials.…”
Section: Methodsmentioning
confidence: 99%
“…In our current program targeted to identify new nitrones for the therapy of stroke 11 , we have already investigated nitrones derived from (hetero)aromatic aldehydes 12,13 , quinolylnitrones [14][15][16][17] , and cholesteronitrones 18 . More recently, we have designed bis-nitrones derived from alpha-phenyl-N-tert-butylnitrone (PBN) ( Fig.…”
mentioning
confidence: 99%